Papyrological investigations: transferring perception and interpretation into the digital world - Tarte, S (Oxford University Press, 2011)
Deciphering ancient and damaged documents is a complex investigative task that papyrologists routinely undertake to extract meaning from the script. Perception and interpretation play an essential role. In this article, we present methods for transferring to the digital world some of the processes that experts draw upon when interpreting a text, with the ultimate aim of constructing an Interpretation Support System (ISS) for papyrologists. Image-capture and image-processing approaches that reflect real-world perceptual processes have been implemented. In addition, we propose an expansion of a previously built model of papyrological reading and transcription. We make explicit some of the implicit processes involved in an interpretation effort, using an example where papyrologists developed hypotheses for the identification of a puzzling letter form. Two distinct yet not mutually exclusive approaches to the interpretation task have been identified: the kinaesthetic/palaeographical strategy and the cruciverbalistic/philological strategy. The ISS will have to facilitate both approaches. Mechanisms triggering the emergence of working hypotheses of interpretation, which we call percepts, have also been pinpointed; they include skilled vision, scholarly expectations, aspect shifting and local-global oscillations. Working hypotheses being triggered by such mechanisms can then be exposed as an explicit network of sourced percepts; these mechanisms also confer a qualitative well-foundedness to the percepts and hence help us to retrace and assess the rationale leading to a specific interpretation. The Author 2011. Published by Oxford University Press on behalf of ALLC and ACH. All rights reserved.